Modeling and parameter identification of a jet-loop bioreactor - Engin, S. N.; Yildiz, F.; Ince, M.; Engin, G. Onkal; Keskinler, B. (IEEE, 2007)
A novel circulating jet-loop membrane bioreactor adapted to high organic matter oxidation has been designed and constructed. Although jet loop bioreactors are still very new to wastewater treatment companies, their advantages over conventional treatment systems make these technologies beneficial, more affordable and consequently, commercially feasible. Since these reactors are capable of treating high organic loads, leachate, which has very complex wastewater characteristics, was used as the input. The focus of this paper is to develop a mathematical model for the jet loop bioreactor in which a near optimal environment is aimed for microorganisms to grow, multiply, and breakdown the high organic content into desired products. Controlling the jet loop bioreactor to achieve high rates of purification possible depends on maintaining the appropriate loadings and operating conditions. This requires collecting various system data to estimate the dynamics of the system satisfactorily with the aim of keeping certain parameters within the specified range. The mathematical model developed for dynamic modeling consists of nonlinear ordinary differential equations describing the dynamics of the cell growth rate and substrate consumption. The differential transform method based solution of the state equations conveniently reveals the current state of the process so that any change in the system parameters can be immediately detected and regulated. The solution also makes the automatic adjustment of the aeration on-off time possible leading to process efficiency and energy save.
Keywords: MEMBRANE BIOREACTOR; MASS-TRANSFER; PERFORMANCE; REACTORS; SLUDGE; Automation & Control Systems; Engineering